Development and testing of a solid core fiber optic delivery system and ultraviolet preionization for laser ignition - Wilvert, Hurley Nicholas, author; Yalin, Azer, advisor; Marchese, Anthony, committee member; Rocca, Jorge, committee member (Colorado State University. Libraries, 2012)
Laser ignition of natural gas engines has shown potential to improve many facets of engine performance including brake thermal efficiency, exhaust emissions, and durability as compared with traditional spark ignition. Laser ignition technology has yet to transition to industry primarily because no system for reliably and safely delivering the laser pulse to the combustion chamber exists. This thesis presents a novel fiber optic delivery approach using solid core multimode step index silica fibers with large cladding diameters (400 μm core, 720 μm cladding). Testing was done on the fibers to determine their response to bending, vibration, high power input, and long duration beam transmission. It was found that in configurations representative of what is required on a real engine, and in the presence of vibration, reliable spark formation could be achieved in pressures as low as 3.4 bar using a specially designed optical spark plug. Comparative tests between the fiber delivered laser ignition system and a traditional J-gap spark plug were performed on a single cylinder Waukesha Cooperative Fuel Research (CFR) engine running on bottled methane. Tests were run at three different Net Mean Effective Pressures (NMEP) of 6, 8, and 12 bar at various air-fuel ratios. Results indicate reliable performance of the fiber and improved engine performance at high NMEP and lean conditions. Thesis research also includes initial studies into the use of dual laser pulses for plasma formation and ignition. In this approach, a first ultraviolet pulse preionizes a volume of air while a second overlapped pulse adds additional energy. Electron density measurements reveal the ultraviolet beam generates substantial preionization even with no visual breakdown, and Schlieren images are used to study the interaction between the two beams at atmospheric and lower pressures.
Keywords: fiber optic; laser ignition